Manejo da desfolha na ecofisiologia da produção de forragem e sementes de azevém anual - Cunha, Ricardo Pereira da (2012)
Annual ryegrass production of (Lolium multiflorum Lam) in Rio Grande do Sul is usually obtained from pasture areas and subsequently deferred pasture. Understanding the physiological ecology of annual ryegrass plant is essential for proper management program, with objective of getting higher forage production and seed. Therefore, the effects of different frequencies of defoliation were measured at (zero, one, two and three) on morphogenesis characteristics of annual ryegrass plants, cultivar BRS Ponteio‟. The following characteristics were evaluated (rate of leaf appearance, phyllochron, leaf expansion rate, rate of leaf senescence, rate of stem expansion, tillering rate and leaf lifespan), forage and seed, and the seed yield components (number of tillers per plant, number of fertile tillers per plant, length of tillers, length of spike, number of spikelets per spike, number of seeds per spikelet and total seed production). The plant behavior was assessed for seven months from (04/29/11 to 11/18/11). Defoliation affected the morphogenesis characteristics, amount of forage and seed harvested of ryegrass cultivar BRS Ponteio‟. The implementation of the second defoliation increased more than 100% the amount of harvested forage in relation to only one defoliation management and without reducing seed yield. The third defoliation contributed significantly to the total harvested forage, but affected negatively the phyllochron, tillering rate and leaf lifespan, and has also reduced seed yield.